A register based system for gene tracking in Duchenne muscular dystrophy. Issue 6 (December 1986) - Read, A P; Kerzin-Storrar, L; Mountford, R C; Elles, R G; Harris, R
Abstract : A total of 102 families with Duchenne muscular dystrophy has been studied with linked DNA polymorphisms as an aid to estimating carrier risks for female relatives. Early work using probes RC8, L1.28, and pXUT23 gave very little clinically useful information because of the high recombination rates between these probes and Duchenne muscular dystrophy and the low proportion of women who were heterozygous. Clinically useful results were obtained using probes 99-6, 754, and particularly pERT87. Examples are given of deductions which can be made using these probes. The importance of a genetic register is stressed as a tool for long term contact with the families and other professionals.